Pengembangan Pompa Sprayer Otomatis Berbasis Mikrokontroler Menggunakan Tenaga Surya sebagai Sumber Energi - Al Fatah, Muhammad Agil; Ali, Salahuddin; Manalu, Abdullah; Rahmawati, Rahmawati (Politeknik Negeri Lhokseumawe, 2025)
The challenges associated with manual irrigation systems, which require significant labor and time, highlight the need for the development of an energy-efficient and environmentally friendly automatic liquid spraying system. This study aims to design and evaluate an automatic sprayer pump system based on a microcontroller (Arduino Mega 2560) powered by a solar panel. The system is controlled using a PS2 joystick remote and utilizes an ultrasonic sensor to monitor the fluid level in the tank. Test results show that the system can operate effectively within a remote control range of up to 30 meters, and the ultrasonic sensor exhibited an average error rate of only 3.22%. Charging with an 80 WP solar panel takes approximately 5 hours to produce 400 Wh of energy. The pump is capable of operating for up to 30 minutes before the battery voltage drops to 11.1 V. With a total energy consumption of 400 Wh, this system is feasible for use in small-scale farming and remote areas.